2022
DOI: 10.9778/cmajo.20210063
|View full text |Cite
|
Sign up to set email alerts
|

Management and clinical outcomes of Lyme disease in acute care facilities in 2 endemic regions of Quebec, Canada: a multicentre retrospective cohort study

Abstract: L yme disease, a multisystem infection primarily caused byBorrelia burgdorferi in North America and by Borrelia afzelii and Borrelia garinii in Europe and Asia, 1,2 progresses in 3 stages: early localized stage, early disseminated stage and late disseminated stage. 3 Cases of Lyme disease reported in Canada increased from 144 in 2009 to 992 in 2016, representing an increase from 0.4 to 2.7 per 100 000 population. 4 In Quebec, Lyme disease has been notifiable since November 2003, with the first locally acquired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…These reports present some results from epidemiological investigations of cases reported between 2016 and 2018 ((8– 11 , 23 , 24 )), such as stage and clinical signs, proportion of cases hospitalized and length of hospitalization. Data published by Musonera et al , (( 14 )), analyzing the medical records of cases reported and treated at a hospital in Estrie and Montérégie between 2004 and 2017 (n=272), were also considered in estimating some clinical criteria not available in the ND (proportion of cases by clinical stage, proportion of cases hospitalized and length of hospitalization).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…These reports present some results from epidemiological investigations of cases reported between 2016 and 2018 ((8– 11 , 23 , 24 )), such as stage and clinical signs, proportion of cases hospitalized and length of hospitalization. Data published by Musonera et al , (( 14 )), analyzing the medical records of cases reported and treated at a hospital in Estrie and Montérégie between 2004 and 2017 (n=272), were also considered in estimating some clinical criteria not available in the ND (proportion of cases by clinical stage, proportion of cases hospitalized and length of hospitalization).…”
Section: Methodsmentioning
confidence: 99%
“…To prepare a clinical portrait of cases reported during our study period, the data published by the DSPu ((8– 11 , 13 , 23 , 24 )) and by Musonera et al (( 14 , 42 )) for the Estrie, Montérégie and Montréal regions were used. The average percentages of cases by stage and clinical signs was estimated based on these data, and the percentages were related to all cases reported in Québec between 2015 and 2019 to estimate the number of cases by stage and clinical signs during our study period.…”
Section: Analysesmentioning
confidence: 99%
See 3 more Smart Citations